Interconnection and Global Cooperation of Alam Melayu in Malay Historiography - Nabila Yasmin (IAIN Syekh Nurjati Cirebon, 2023)
Alam Melayu has been historically recognized as a significant geographical point that connects the Western and Eastern worlds. It is a strategic location in which trade and other activities occur between nations. The geographical characteristics enhance the establishment of relations and cooperation in various aspects such as economics, intellectual religion, politics, and culture. Therefore, this research aimed to describe the forms of contact and collaboration between Alam Melayu and foreign nations mentioned in Islamic Malay historiography. Content analysis and historiographical approach were applied as part of the methodology. Furthermore, some of the selected primary sources included the works of Hikayat Raja Pasai, Sejarah Melayu, and Hikayat Aceh. This early Islamic Malay historiography provided a fundamental, historic overview, alongside the openness and connection of Alam Melayu to culture and trade from the outside world.